2015
DOI: 10.15353/cfs-rcea.v2i2.97
|View full text |Cite
|
Sign up to set email alerts
|

GRAB - GMO 2.0: Genetically modified crops and the push for Africa’s green revolution

Abstract: Genetically modified (GM) crops are plants in which the DNA has been engineered using laboratory techniques to express a beneficial trait. Their reception across the globe has been mixed: they form a dominant part of North American agriculture, they have been met with widespread disapproval in Europe, and they are of increasing importance in emerging economies such as India, China and Brazil. Approximately 9 percent of agricultural land worldwide was planted under GM crops in 2014. This figure expanded at a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Extensive scholarship has documented that these critiques are a central reason for opposition or concern regarding GM. Key examples include concerns about the continuing expansion of industrial agriculture and the failure to address broader issues such as food insecurity (Fitting 2011; Holt Giménez and Shattuck 2011; Stone 2002; Tomlinson 2013; Schnurr 2015) or corporate control of intellectual property (Patel 2009; McAfee 2003; Carolan 2008). With GE, Helliwell, Hartley, and Pearce (2019) have found that actors such as non-governmental organizations (NGOs) may be reframing debates on GE, focusing not just on the veracity of benefit and risk claims but on questions like “is this truly necessary?” In studying GD for polled dairy cattle, Ritter et al (2019) found that attitudes varied depending on the stated purpose provided to study participants, with participants more likely to view the application favorably if the purpose was animal welfare, as opposed to cost savings, or no stated purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive scholarship has documented that these critiques are a central reason for opposition or concern regarding GM. Key examples include concerns about the continuing expansion of industrial agriculture and the failure to address broader issues such as food insecurity (Fitting 2011; Holt Giménez and Shattuck 2011; Stone 2002; Tomlinson 2013; Schnurr 2015) or corporate control of intellectual property (Patel 2009; McAfee 2003; Carolan 2008). With GE, Helliwell, Hartley, and Pearce (2019) have found that actors such as non-governmental organizations (NGOs) may be reframing debates on GE, focusing not just on the veracity of benefit and risk claims but on questions like “is this truly necessary?” In studying GD for polled dairy cattle, Ritter et al (2019) found that attitudes varied depending on the stated purpose provided to study participants, with participants more likely to view the application favorably if the purpose was animal welfare, as opposed to cost savings, or no stated purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The restrictive patents and high costs that stymied the adoption of this first generation of GM crops precipitated a concerted effort on the part of development donors to create GM versions of African staple crops that would be unencumbered by either (Schnurr, 2015). At the turn of the 21st century, the Rockefeller Foundation partnered with biotech giants to form the African Agricultural Technology Foundation (AATF) to mediate agreements between private seed companies and African scientists, believing that such a partnership would allow for African farmers to access technologies that would otherwise be inaccessible behind patents (Schurman, 2017).…”
Section: Joeva Sean Rock Et Almentioning
confidence: 99%
“…Tomlinson 2013; Schnurr (2015) In facing the proposition of gene editing, the organic community is affirming many of the older concerns regarding GM, but doing so in direct response to the new arguments specific to gene editing that proponents are asserting. This "boundary maintenance" involves the ongoing work of bolstering and rearticulating existing boundaries between genetically engineered and organic (Haraway, 1997, p. 67).…”
Section: Jeopardizing Farmer Livelihoodsmentioning
confidence: 99%